2004
DOI: 10.1007/s11663-004-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of particle size on the laser sintering of iron powder

Abstract: A. SIMCHI The effects of powder particle size on the densification and microstructure of iron powder in the direct laser sintering process were investigated. Iron powders with particle sizes ranging from 10 to 200 m were used. It was found that the sintered density increases as the laser energy input is increased. There is, however, a saturation level at which higher density cannot be obtained even at very intensive energy input. This saturation density increases as the size of the iron particles decreases. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 13 publications
2
80
0
4
Order By: Relevance
“…This was possibly due to the reduced surface-volume ratio, which tends to reduce the kinetics of densification. The result is similar to the previous study by Simchi with iron powders in which finer particles need less energy due to the enhancement of densification kinetics [23].…”
Section: Effect Of Particle Size On the Processing Windowsupporting
confidence: 90%
See 1 more Smart Citation
“…This was possibly due to the reduced surface-volume ratio, which tends to reduce the kinetics of densification. The result is similar to the previous study by Simchi with iron powders in which finer particles need less energy due to the enhancement of densification kinetics [23].…”
Section: Effect Of Particle Size On the Processing Windowsupporting
confidence: 90%
“…It is known that a greater surface-volume ratio of finer powders leads to higher amounts of laser energy absorption, thereby increasing the temperature and sintering kinetics [23]. It was found that this phenomenon is applicable to both the CO 2 and the Nd:YAG lasers.…”
Section: Effect Of Particle Size On the Processing Windowmentioning
confidence: 94%
“…The powder particles used should be free of defects such as satellites and inter-agglomerate pores, because the presence of such defects can cause lack of fusion between the particles affecting the densification behaviour. The distribution of the powder particle sizes also affects the flowability of the powders as fine powders with a narrow particle size distribution tend to agglomerate and coarse particles with a broader particle size distribution tend to segregate leading to process instabilities [88]. The fraction of smaller particles should be as small as possible to avoid inhomogeneous distribution of the powder over the build platform as friction among the particles increases with decrease in the particle size [29,59].…”
Section: Effects Of Powder Properties On the Slm Densification Mechanismmentioning
confidence: 99%
“…roughness) for SLS-fabricated polymer parts. Studies on the laser sintering of iron powder showed that the processing parameters such as laser power, scan rate, scan line spacing, thickness of layer, and scanning geometry and sintering atmosphere [3] and the characteristics of the powder material such as particle size (PS) and PS distribution [4] affect the densification behaviour and the attendant microstructural features. Shi et al [5] investigated the effect of the material properties of the polymer on the quality of SLS parts and found that the PS of the powder affected not only the precision, but also the density of the SLS-fabricated parts.…”
Section: Introductionmentioning
confidence: 99%